Sistem Pendidikan di China - Salsabila Faruza Nasution; Mislaini Mislaini; Faizah Fitrah (Universitas Palan, 2025)
The education systems in China and Indonesia have significant differences, although both aim to create an educated generation. In China, education focuses on the development of technical and academic skills with a highly structured and competitive system, especially through the Gaokao exam that determines students’ academic futures. Meanwhile, Indonesia places more emphasis on cultural diversity and character development, with a more inclusive learning approach based on social values. These differences are clearly reflected in the educational structure, curriculum, teaching methods, and assessment systems, which align with the social and economic needs of each country.